Augmented neutralization of SARS‐CoV‐2 Omicron variant by boost vaccination and monoclonal antibodies. Issue 6 (23rd March 2022) - Schulz, Sebastian R.; Hoffmann, Markus; Roth, Edith; Pracht, Katharina; Burnett, Deborah L.; Mazigi, Ohan; Schuh, Wolfgang; Manger, Bernhard; Mielenz, Dirk; Goodnow, Christopher C.; Christ, Daniel; Pöhlmann, Stefan; et al.
Abstract: Effective vaccines and monoclonal antibodies have been developed against coronavirus disease 2019 (COVID‐19) caused by severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). However, the appearance of virus variants with higher transmissibility and pathogenicity is a major concern because of their potential to escape vaccines and clinically approved SARS‐CoV‐2‐ antibodies. Here, we use flow cytometry‐based binding and pseudotyped SARS‐CoV‐2 neutralization assays to determine the efficacy of boost immunization and therapeutic antibodies to neutralize the dominant Omicron variant. We provide compelling evidence that the third vaccination with BNT162b2 increases the amount of neutralizing serum antibodies against Delta and Omicron variants, albeit to a lower degree when compared to the parental Wuhan strain. Therefore, a third vaccination is warranted to increase titers of protective serum antibodies, especially in the case of the Omicron variant. We also found that most clinically approved and otherwise potent therapeutic antibodies against the Delta variant failed to recognize and neutralize the Omicron variant. In contrast, some antibodies under preclinical development potentially neutralized the Omicron variant. Our studies also support using a flow cytometry‐based antibody binding assay to rapidly monitor therapeutic candidates and serum titers against emerging SARS‐CoV‐2 variants. Abstract : Using pseudotype neutralization and flow cytometry‐based spike protein binding assays, Schulz and colleagues show that a boost with BNT162b2 increased neutralizing antibody responses against Omicron, albeit less than against the Wuhan strain and the Delta variant. In contrast, most clinically approved monoclonal antibodies failed to recognize the Omicron variant.